Coplexes in abelian categories - POP, Flaviu (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
Starting with a pair F : A +== B : G of additive contravariant functors which are adjoint on the right, between abelian categories, and with a class U , we define the notion of (F, U )-coplex. Considering a reflexive object U of A with F(U ) = V projective object in B, we construct a natural duality between the category of all (F, add(U ))-coplexes in A and the subcategory of B consisting in all objects in B which admit a projective resolution with all terms in the class add(V ). Mathematics Subject Classification (2010): 16E30, 16D90.